How Hedonic Motives and Impulsive Shopping Tendencies Shape Gen-Z Online Shopping Behavior - Antonius Felix; Arta Moro Sundjaja; Yuvaraj Ganesan; Akbar Lufi Zulfikar (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2026)
This study aims to determine the effect of hedonic motives on the online shopping behavior of Generation Z consumers in Shopee Mall, Jakarta with impulsive shopping tendencies (IST) as a mediating variable. A quantitative cross-sectional survey was conducted based on the Stimulus-Organism-Response (S-O-R) theory and the Theory of Planned Behavior (TPB). A total of 155 valid respondents were selected by purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.1.1.5. The measurement model demonstrated adequate convergent validity (outer loadings 0.722–0.840; AVE > 0.50), discriminant validity (HTMT criterion; Henseler et al., 2015), and composite reliability (0.842–0.873). Structural model results indicate that hedonic motives significantly and positively influence impulsive shopping tendencies (β = 0.518, p < 0.001) and online shopping behavior directly (β = 0.395, p < 0.001). Impulsive shopping tendencies also significantly predict online shopping behavior (β = 0.367, p < 0.001). The combined model explains 44.1% of variance in online shopping behavior. These findings confirm the partial mediation role of impulsive shopping tendencies in the hedonic motives–online shopping behavior relationship. The study contributes theoretical extensions of S-O-R to premium e-commerce platforms and provides practical implications for platform operators seeking to leverage hedonic engagement while promoting responsible consumption among young consumers.